EFEKTIVITAS PENGENDALIAN INTERNAL DENGAN PENERAPAN SISTEM INFORMASI AKUNTANSI (SIA) PENJUALAN - Repa, Reren Yolanda; Nainggolan, Karlonta; Adlina, Hafizah (Journal Business Administration: Entrepreneurship and Creative Industry, 2022)
The study is aimed at seeing how corporate incomes are applied and whether the implementation of sales increases the effectiveness of internal controls. The study USES descriptive and decryptive qualitative research with the questionnaire as his instrument. Data collection techniques through observation and interview activities. The process of data analysis is done using data normality tests and simple linear regression tests. The result of data analysis is known that its significance value (sig) is as great 0,803 Bigger than 0,05, therefore, h0 received is denied, which means that "the adoption of sia (x) does not increase the effectiveness of internal control (y) 0.002, This means that variables (application) of variables are numerical 2% While the rest is affected by other variables, the result can be concluded that the application of sia (x) affects internal control (y) with total relationships 2% as for 98%Â  Internal control is linked to other uninspected variables.